Islam in the Mediatization of the Straight Edge Scene: a Case Study of Positive Youth Indonesia's Instagram Visual Communication - Bhaskara, Hilman Ahdi (Universitas Brawijaya, 2024)
Mediatization is an area of media that connects certain thought-building with other media or different content. Positive Youth Indonesia as a punk community with the Straight Edge scene, is trying to mediate the teachings of Islam in its social campaign on Instagram. The social campaign is in the form of a series of propaganda posters and social activities. In this regard, this study aims to reveal the mediatization of Straight Edge which brings elements of Islamic teachings as well as visual culture acculturation that is applied in it. The study uses a descriptive qualitative method with a society in spectacle approach as well as literature studies related to multidisciplinary regarding the Straight Edge sub-culture scene and social campaigns from the point of view of visual communication design. The results of this study indicate that there is mediatization of the Straight Edge scene by incorporating elements of Islamic theories and the acculturation of Islamic visual culture in each Instagram post. The mediatization arises repeatedly in every online and offline social campaign program using the visual style and language of Straight Edge's punk sub-culture .The existing acculturation of Islamic visual culture is presented ideologically and conceptually which blends with Straight Edge's visual style.